Independent Evaluation of headspace: the National Youth Mental Health Foundation: Evaluation Plan - Muir, K; McDermott, S; Katz, I; Patulny, R; Flaxman, S; Gendera, S (UNSW Sydney, 2008)
headspace aims to promote improvements in the mental health, social well-being and economic participation of Australian young people aged 12-25 years. headspace has a particular focus on early identification and intervention for young people at risk of developing mental health problems, and those already showing early signs of mental health problems or associated drug and alcohol problems. The headspace model involves the establishment of Communities of Youth Services (CYSs), which provide integrated and coordinated psychiatric, medical, allied health and vocational services in a primary care setting. CYSs provide young people at risk of mental health and related disorders with appropriate, youth-friendly support and treatment for mental health, drug and alcohol, and vocational problems. The CYSs promote early help-seeking and advocate early intervention and the use of evidence-based treatment and care. The independent evaluation of headspace (2008-2009) will examine the achievements, limitations and future directions of the program. This plan outlines the methodology for the evaluation of headspace.
SPRC Report Series 20/08
Keywords: Australia; Youth; Mental Health; headspace; Communities of Youth Services